2001
DOI: 10.1116/1.1335685
|View full text |Cite
|
Sign up to set email alerts
|

Absolute intensities of the vacuum ultraviolet spectra in oxide etch plasma processing discharges

Abstract: @In this paper, we report the absolute intensities of ultraviolet light between 4.9 eV and 24 eV ( 250 m-n to 50 mn ) striking a silicon wafer in a number of oxide-etch processing discharges. Our emphasis is on photons with energies greater than 8.8 eV, which have enough energy to damage Si02. These discharges were in an inductively-driven Gaseous Electronics Conference reference cell which had been modified to more closely resemble commercial etching tools. Comparisons of measurements made through a side port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…5 During plasma processing, both ion bombardment and vacuum ultraviolet (VUV) irradiation can occur. [6][7][8][9] Defect states (and subsequent trapped charge) generated by both VUV irradiation and charged-particle bombardment of low-k dielectrics have been shown to adversely affect the capacitance, 10-12 breakdown voltage, 13 and leakage currents 14,15 in addition to causing chemical and structural changes 16 in organosilicate dielectrics. In this letter, it is shown that both photons and charged particles emitted during plasma processing have a deleterious effect on the time to dielectric breakdown, i.e., the dielectric lifetime.…”
mentioning
confidence: 99%
“…5 During plasma processing, both ion bombardment and vacuum ultraviolet (VUV) irradiation can occur. [6][7][8][9] Defect states (and subsequent trapped charge) generated by both VUV irradiation and charged-particle bombardment of low-k dielectrics have been shown to adversely affect the capacitance, 10-12 breakdown voltage, 13 and leakage currents 14,15 in addition to causing chemical and structural changes 16 in organosilicate dielectrics. In this letter, it is shown that both photons and charged particles emitted during plasma processing have a deleterious effect on the time to dielectric breakdown, i.e., the dielectric lifetime.…”
mentioning
confidence: 99%
“…Charge separation causes the dielectric to become polarized, which also contributes to the surface potential of the dielectric. To separate the damage effects, plasma-generated VUV radiation from charged-particle bombardment, we used monochromatic synchrotron radiation in the same photon energy range that is typically found in most processing plasmas [1]- [3]. The synchrotron source at the University of Wisconsin, Madison was used as a source of VUV photons to expose unpatterned dielectric-coated wafers.…”
mentioning
confidence: 99%
“…For these reasons, very little relevant data on this topic can be found. 21,22 According to Woodworth et al, the dominant emission lines in the v-UV region with our plasma etching process (CF 4 /CH 2 F 2 /Ar) likely originate from argon emission at 105 nm and hydrogen emission at 103 nm and 122 nm. In addition, fluorine emission lines at 79 nm and 98 nm, fluorocarbon emission lines (above 190 nm), and carbon emission lines spread throughout the whole spectrum are also expected to significantly contribute to the plasma emission in the v-UV.…”
Section: Plasma Treatmentsmentioning
confidence: 98%
“…In addition, fluorine emission lines at 79 nm and 98 nm, fluorocarbon emission lines (above 190 nm), and carbon emission lines spread throughout the whole spectrum are also expected to significantly contribute to the plasma emission in the v-UV. 22 With regards to O 2 plasma, the major emission lines are expected from oxygen around 130 nm. For both plasma processes, additional emission lines at lower wavelengths may be present but have not been observed experimentally during plasma etching.…”
Section: Plasma Treatmentsmentioning
confidence: 99%